ANALYSIS OF EARNINGS GROWTH AND DIVIDENDS ON STOCK RETURNS - Andolo, Clarti Welhemina; Pandeirot, Lanemey Brigitha (Faculty of Economics and Business, 2025)
Investors need information to help make the right investment decisions. One of the considerations for investors to make investment decision in a company is the company's stock return and thus, investors do need to know the variables that can affect stock returns. For this reason, this study was conducted with the aim of determining whether earnings growth and dividends have a significant effect on stock returns. This study utilizes secondary data from financial sector companies whose shares are traded on the Indonesia Stock Exchange during the Covid 19 pandemic, namely from 2019 to 2021. The results of data sorting using the purposive sampling method obtained 59 financial sector companies that met the requirements in this study. Using multiple linear regression tests, the results of the study found that earnings growth had an effect on stock returns, while dividends were found have no effect on stock returns. These results provide input that can be used by further research and investment in making the right investment decisions.